(3eZGfi GdCNjGQ aj CSGei QLGd eYGfi GdGKGQs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO Hg JQLeI GHQGgje Hf YHO Gddg Hf Mfjf GdgGTei s
(3BNQgG (B:s
(3CHh GdUgHGA GdcHQi GdHUQi hjbGd (B: (3G deOfi ehdi Hf YHGS s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B213 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B562s
Keywords: (3eJaQbGJs